Ingresso, acesso e permanência dos alunos com necessidades educacionais especiais na Universidade Federal de Santa Maria - UFSM - RS - Pellegrini, Cleonice Machado de (2006)
The study aimed at investigating the Admittance, Access and Permanence of Students with Special Educational Needs in the Federal University of Santa Maria (UFSM), Rio Grande do Sul State, Brazil. To identify the research individuals, it was first necessary to interview the fifty-eight coordinators of the undergraduate courses offered by the institution at eight different campus facilities. Thereafter, the research individuals were selected, that is, the students with Special Educational Needs duly enrolled in undergraduate courses within the institution. The empirical field was the Federal University of Santa Maria (UFSM). This research was based upon the inclusion principle, which considers everybody is entitled to the right to Education, no matter the difficulties, conditions or differences. From the political and social point of view, all educational institutions elementary, secondary or university need to adjust to, recognize and meet these students needs. The qualitative research has used semi-structured interviews, breaking itself of micronsystem until reaching macrosystem, what it was characterized for the methodology of the concentrically circles, being with this gotten the results that show the existing architectural and attitudinal barriers within the institution context. Final considerations highlight the importance of awareness, changes and reforms to eliminate architectural barriers and environmental adverse factors, as well as attitudinal barriers impairing the inclusion of students with Special Educational Needs. We could also highlight the need to increase the scarce mapping studies on these students, in order to locate them and supply them with the deserved conditions to remain in the institution, as well as developing institutional actions to meet their expectations, thus assuring Education for All. Respect for diversity makes us thinking about the importance of understanding the different special conditions that will determine the performance of the school activities by those students with special educational needs within their setting. All school environments are linked to knowledge production and spread; for this reason, awareness, knowledge and respect of these special conditions are essential within this context.